A Review of Current Issues Underlying Colon Cleansing before Colonoscopy. (2007) - Hookey, Lawrence C; Vanner, Stephen
Abstract : The present review examines four current issues related to the efficacy, patient tolerance and safety of the following bowel cleansing agents: oral sodium phosphate (NaP), polyethylene glycol (PEG) and magnesium citrate (Pico-Salax, Ferring Pharmaceuticals Inc, Canada), an agent recently made available in Canada. MedLine and PubMed databases were systematically searched to identify studies related to the efficacy of altered PEG solutions combined with adjunct treatments; the efficacy, tolerability and safety of Pico-Salax; the association between nephrocalcinosis, and chronic renal failure and oral NaP use; and the role of diet. Although lower volume PEG solutions combined with adjuvant agents were generally associated with better patient tolerance, their efficacy was varied and interpretation of this end point is complicated by study design issues. There are very few reported studies of Pico-Salax, and as a result, there are insufficient data to draw conclusions about the efficacy of this agent. The available data suggest that Pico-Salax may be better tolerated by patients, than oral NaP and PEG solutions. There is a paucity of hemodynamic monitoring data pre- and postadministration, but the available data suggests that this small-volume osmotic agent could cause subclinical contraction of the intravascular space. Recent case reports suggest an association between nephrocalcinosis and oral NaP ingestion, but to date, these reports have been confined to a single centre. Preliminary studies suggest that this is not a widespread problem, but more studies are needed. There are only a few studies examining diet and patient tolerability, but they do suggest that diet may be liberalized with some cleansing regimens to enhance tolerability without decreasing efficacy. The present review highlights current controversies and advances in colon cleansing before colonoscopy, and also identifies areas for further study.